Pathogenesis and Antifungal Drug Resistance of the Human Fungal Pathogen Candida glabrata - Karl Kuchler; Tobias Schwarzmüller; Michael Tscherner (MDPI AG, 2011)
Candida glabrata is a major opportunistic human fungal pathogen causing superficial as well as systemic infections in immunocompromised individuals and several other patient cohorts. C. glabrata represents the second most prevalent cause of candidemia and a better understanding of its virulence and drug resistance mechanisms is thus of high medical relevance. In contrast to the diploid dimorphic pathogen C. albicans, whose ability to undergo filamentation is considered a major virulence trait, C. glabrata has a haploid genome and lacks the ability to switch to filamentous growth. A major impediment for the clinical therapy of C. glabrata infections is its high intrinsic resistance to several antifungal drugs, especially azoles. Further, the development of antifungal resistance, particularly during prolonged and prophylactic therapies is diminishing efficacies of therapeutic interventions. In addition, C. glabrata harbors a large repertoire of adhesins involved in the adherence to host epithelia. Interestingly, genome plasticity, phenotypic switching or the remarkable ability to persist and survive inside host immune cells further contribute to the pathogenicity of C. glabrata. In this comprehensive review, we want to emphasize and discuss the mechanisms underlying virulence and drug resistance of C. glabrata, and discuss its ability to escape from the host immune surveillance or persist inside host cells.